Nonlinear load-frequency control: An approach using optimized hierarchical fuzzy systems - Baydokhty, Mohsen Ebrahimian; Zeynal, Hossein; Zare, Assef (2016 24th Iranian Conference on Electrical Engineering (ICEE), 2016)
Load Frequency Controllers (LFC) has long been handled by PID techniques. However, nonlinear disturbance in power system caused PID controllers exhibiting a mediocre performance. As an alternative, Fuzzy Mamdani and Takagi Sugeno Kang Fuzzy (TSKF) controllers were predominantly employed. However, the computational intractability due to torrential fuzzy rules limits further use of these techniques. As a result, an Optimal Hierarchical Takagi Sugeno Kang Fuzzy (OHTSKF) controller is proposed. In this model, TSFK breaks into several sub-systems and through hierarchical classification, extensive number of fuzzy rules is eliminated, reducing the executional time of solution. Further, the Cuckoo Optimization Algorithm (COA) is integrated into the model so as to improving the response quality subject to nonlinear load disturbance. Simulation results demonstrated that the proposed OHTSKF controller surpasses other Fuzzy Mamdani and TSKF and it can replace other techniques and be served as an efficient LFC system for utilities.